Expanding the phenotype of RTTN variations: a new family with primary microcephaly, severe growth failure, brain malformations and dermatitis. Issue 5 (29th April 2016) - Grandone, A.; Torella, A.; Santoro, C.; Giugliano, T.; del Vecchio Blanco, F.; Mutarelli, M.; Cirillo, M.; Cirillo, G.; Piluso, G.; Capristo, C.; Festa, A.; Marzuillo, P.; et al.
Abstract : Primary autosomal recessive microcephaly (MCPH) is a developmental disorder characterized by prenatal onset of abnormal brain growth. MCPH occurs both alone and as part of a broad range of neurodevelopmental syndromes with or without cortical malformations and growth retardation. Here we report a consanguineous Moroccan family with two siblings affected by severe primary microcephaly, failure to thrive, congenital dermatitis and severe developmental delay. Brain magnetic resonance imaging showed lissencephaly of frontal lobes and periventricular heterotopia of the gray matter. We performed both Comparative Genomic Hybridization array and whole exome sequencing (WES) analyses of the kindred. No quantitative defects were detected. However, WES identified a new homozygous missense variation in the penultimate nucleotide of exon 23 of RTTN gene (c.2953A>G;pArg985Gly). cDNA sequencing revealed two abnormal spliced products, one lacking only exon 23 and the other lacking exons 22 and 23 (out‐of‐frame). RTTN is a protein involved in cilia structure and function. Homozygous mutations in RTTN gene have been described in bilateral diffuse isolated polymicrogyria and, more recently, in microcephalic primordial dwarfism (PD). We found a novel homozygous mutation in RTTN associated with microcephalic PD as well as complex brain malformations and congenital dermatitis, thus expanding the phenotypic spectrum of both RTTN ‐associated diseases and ciliary dysfunction. Abstract :